PENGARUH PERMASALAHAN TRANSPORTASI TERHADAP RUANG PUBLIK - Setiawan, Altim (MEKTEK, 2005)
This paper is to describe the effect of transportation problem on public space and sample cause in Bandung West Jawa. Proceded by introduction to transportation, problem and conflict which is caused by urban design, sample cause in Bandung and some conceps which is discussed transportation system by side of urban design. The discussion use literature review methods and to compare with field condition by existing regulation. Â